Factors Affecting Contractors' Bidding Decisions for Construction Projects in Nigeria - Oyeyipo, Opeyemi Olanrewaju; Odusam, Koleola Tunwase; Ojelabi, Rapheal Abiodun; Afolabi, Adedeji Olushola (Penerbit Universiti Sains Malaysia, 2016)
Bidding is the most common means by which contractors obtain work. The construction industry accounts for approximately three quarters of the Gross Domestic Product (GDP) in the country. It is generally believed that wrong bidding practice is a major contributor to the construction industry's inefficiency. This means that any improvement in bidding has the potential to enhance the industry's performance, improve the quality of the decision-making process and assist in achieving the strategic objective of contracting organisations. In an effort to uncover the main factors that characterise the bid/no bid decision of contracting organisations, a study to evaluate the factors that affect contractors' decisions to bid for a project and to evaluate the importance of the identified factors to decision makers was conducted. A structured questionnaire was used as the principal instrument for collecting data from respondents. A total sample of 100 was drawn from these collections of construction contractors from Lagos state. Fifty were completed and returned, representing a 50% response rate. Frequency, percentage, mean score and Spearman's correlation were used in analysing data collected for the study. The results indicate that the financial capability of clients, availability of capital and availability of material are the most important factors that contractors consider when making a bid/no bid decision. The study also reveals that competition (number and identity of competitors) does not have significant influence on contractors' bidding decisions. The study recommends that contractors should also build their reputations in the construction industry by acquiring technical competencies and capabilities as these qualities have become important considerations in assessing contractors' competiveness, as well as being key indicators of successful tendering in construction projects